An exploratory study of how young people experience and perceive living with type 1 diabetes during late adolescence and emerging adulthood. (December 2021) - Ingersgaard, Marianne Vie; Hoeeg, Didde; Willaing, Ingrid; Grabowski, Dan
Objective: Suboptimal glycemic control and psychosocial challenges are significant concerns for adolescents and emerging adults (collectively young people) with type 1 diabetes. Knowledge about young peoples' attitudes towards living with type 1 diabetes is inadequate, but the issue is important in the development of strategies to improve glycemic control and psychosocial well-being. This study explored young peoples' perceptions of living with type 1 diabetes. Methods: An exploratory, qualitative design was employed. Data were collected through five participatory workshops with 19 young people (age 15–25). Data were thematically analyzed. Results: The overall depiction of living with type 1 diabetes was paradoxical; it affected everything and nothing. Living with type 1 diabetes was a balancing act between accommodating a "normal" way of living and self-management tasks of the treatment regimen. Participants' perceptions reflected shifting accounts that could be divided into five themes: (1) special rules during youth, (2) striving for autonomy, (3) an uncertain future, (4) social support, and (5) stigma and disclosure. Discussion: It is important to probe for the multiple and interrelated social contexts that underlie young peoples' motives for adhering to and deviating from treatment regimens. Future studies should focus on relational aspects, including stigma mechanisms, the role of friends, and facilitation of balanced parental involvement.